(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Language learning is one of the important processes for cognitive, social and personal development of a person. The success of this process depends on many factors, one of which is motivation. Motivation plays an important role in increasing interest, persistence and effort in language learning. The study of the topic of language learning motivation is widely researched in the field of psycholinguistics, because motivation has a positive effect on the language learning process. This article examines the role of motivation in language learning, types of motivation and its psycholinguistic aspects.